2013
DOI: 10.3892/etm.2013.1277
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated modification and anti-tumor activity of laminarin

Abstract: The aim of this study was to investigate the sulfated modification of laminarin and the changes in structure and antitumor activity. The chlorosulfonic acid-pyridine method was applied for sulfated modification. The molecular weights of laminarin and laminarin sulfate (LAMS) were measured by high-performance liquid chromatography (HPLC), and IR and NMR spectra were also recorded. The surface conformations of laminarin and LAMS were observed with a scanning electron microscope. The antitumor activities of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…4, respectively. The current work is comparable with previous research by Ji et al, [16], which analyzed laminarin and sulfated laminarin in the area of 1 H-NMR spectrum of δ 4.49-5.5 ppm. Thus, these spectra indicate that the glycosidic bonds in both G (Fig.…”
Section: Nmr Spectroscopysupporting
confidence: 92%
“…4, respectively. The current work is comparable with previous research by Ji et al, [16], which analyzed laminarin and sulfated laminarin in the area of 1 H-NMR spectrum of δ 4.49-5.5 ppm. Thus, these spectra indicate that the glycosidic bonds in both G (Fig.…”
Section: Nmr Spectroscopysupporting
confidence: 92%
“…3A) in SLBS11P and fucoidan standard indicates stretching vibrations of the glycosidic C─O group of fucoidan. The broadened peak between 1,120-1,270 cm -1 indicate sulfate groups (S═O RB3LYP/6-31G(d,p) level and based on relevant literature (Tul'chinsky et al 1976, Christiaen and Bodard 1983, Mathlouthi and Koenig 1987, Mollet et al 1998, Roberts and Quemener 1999, Marais and Joseleau 2001, Pereira et al 2003, Chandía et al 2004, Praiboon et al 2006, Leal et al 2008, Alves et al 2010, Ji et al 2013, Xia et al 2014). Fig.…”
Section: Cytotoxicity and Protective Effects Of Cpsmentioning
confidence: 99%
“…Their results revealed that incubation of cancer cells with laminaran (400-1600 μg/mL) for 72 h induces apoptosis in LoVo cells. Additionally, Ji et al [248] studied anticancer activity of laminaran after modifying the sulfate content of laminaran by the chlorosulfonic-acid-pyridine method. The authors compared the anticancer effects of normal and modified laminaran on LoVo cells by the 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) assay.…”
Section: Biological Activities Of Laminaranmentioning
confidence: 99%
“…However, at the same concentration, unmodified laminaran could reduce the cancer cell number by only 38%. Thus, the authors proposed that sulfation of the structure might increase bioactivities of laminaran [248].…”
Section: Biological Activities Of Laminaranmentioning
confidence: 99%